(3EOGQI GdHfhc (B((3c(B20) (3GdLRA GdChd (B/s - (3CHh RjO, MGeO GdOShbjs ((3GdbGgQI(B: s (3eWHYI eQcR GdJYdje GdeaJhM(B, s)
(3GdHfhc hGdJfejI GdGbJUGOjI h GdGLJeGYjI aj eUQ, gjcd GdLgGR GdeUQaj GdeUQj,GdGfTWI GdQFjSjI ddHfhc GdJLGQjI, GdGfTWI GdQFjSjI ddHfhc ZjQ GdJLGQjI, GdhOGFY GdebOeI aj GdShb GdeUQj GdeUQaj, GdJSgjdGJ GdGfJeGFjI GdebOeI aj GdShb GdeUQj GdeUQaj, YedGA GdNOeI GdGfJeGFjI, GSJKeGQGJ GdHfhc aj GdShb GdeUQaj GdeUQjs
(3eQGLY U(B.270s
Keywords: (3GdHfhcs; (3GdJfejI GdGbJUGOjIs